The impact of cancer therapy on cognition in the elderly - Mandilaras, Victoria; Wan-Chow-Wah, Doreen; Monette, Johanne; Gaba, Francine; Monette, Michele; Alfonso, Linda (Frontiers in Pharmacology, 2013)
Cancer and cancer therapy-related cognitive impairment (formerly known as chemobrain or chemo-fog) are often described in the literature. In the past, studies have failed to prove the existence of cancer therapy-related cognitive dysfunction. However, more recently, prospective trials have shown that patients undergoing chemotherapy do display impairment in specific cognitive domains. Aging confers an increased risk of developing cancer, as well as cognitive impairment. The Geriatric Oncology clinic of the Segal Cancer Centre, Jewish General Hospital in Montreal was founded in 2006 to address the unique needs of older cancer patients. We will describe two cases of cancer therapy-related cognitive impairment from our Geriatric Oncology clinic. The first case is that of a 75 year old male diagnosed with stage III non-small cell lung carcinoma who complained of forgetfulness since starting carboplatin-paclitaxel. The second case is that of a 65 year old female diagnosed with stage I, ER positive breast cancer who had undergone lumpectomy followed by adjuvant CMF chemotherapy, radiation therapy and was on exemestane when she was evaluated. We will also briefly review the literature of cancer therapy-related cognitive impairment.